The implementation of quantum learning strategies in ecology materials to enhance students' creative thinking skills - Hartono, Adi; Sarjani, Tri Mustika; Fitria, Dini; Sulaiman, Nanda Fahira (JPBIO (Jurnal Pendidikan Biologi), 2025)
Creative thinking is a key 21st-century skill that must be fostered in science education, particularly in ecology, which demands conceptual understanding and contextual problem solving. However, classroom learning often relies on conventional methods that limit student engagement and creativity. This study examines the effect of quantum learning strategies on improving students’ creative thinking skills in ecology. Quantum learning was selected for its holistic approach that integrates emotional, intellectual, and social dimensions, potentially optimizing creative stimulation. The research employed a quasi-experimental design with a pretest–posttest control group. Participants were 10th-grade students at SMA Negeri 11 Medan, divided into experimental and control groups. Data were collected using ecology-based creative thinking tests. The findings revealed a significant improvement in the creative thinking abilities of students in the experimental group compared to those in the control group. These results demonstrate that quantum learning effectively enhances students’ creativity in ecological learning contexts. The study suggests that adopting quantum learning strategies can help educators design more engaging and innovative learning environments aligned with 21st-century educational demands.